Management Accountants’ Functions and Control System in Informal Sector’s Business Decisions in Nigeria (International Journal of Scientific Research and Management (IJSRM), 2015)
This paper examined the effects of Ownership-Controls and Management Accountant(s) functions indecision making process of informal businesses (SMEs) in Osun State of Nigeria. Disparity cases that areoften experienced by Management Accountants on decisions and that of business Owners in informalbusiness sectors – One-man businesses, partnership businesses and other private companies necessitate thisstudy. Many Accountants in the informal business sectors are suffering from a lot of hardships through self - designed decisions usually imposed by business Owners at the expense of information generated throughcalculated parameters on business decisions. The study used both Simple Percentage Method andDescriptive Data Analysis Method (DDAM) to evaluate 10 informal businesses in Osogbo, the capital city ofOsun State of Nigeria. The study revealed that most informal Businesses failed due to the fact that Ownersare always ignoring the advice of Management Accountants in vital business decisions. The paperrecommends proper utilization of MCS principles in line with information supplied by ManagementAccountants in both formal and informal sectors of Nigeria economy so as to aid the function and servicedeliverance potentials and subsequent improvement in SMEs results in Nigeria.